2016
DOI: 10.1007/s00038-016-0795-y
|View full text |Cite
|
Sign up to set email alerts
|

Decreased smoking initiation among male youths in China: an urban–rural comparison

Abstract: Decreased smoking initiation appears to be associated with birth year, which may be correlated with social and economic development of China in conjunction with an unprecedented rate of urbanization. Results suggest that the rate of smoking initiation for male youths may experience further decreases, particularly in areas with a heightened potential of urbanization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“… 23 Results in research suggested that the rate of smoking might experience further decreases in areas with a heightened potential of urbanization. 24 People in the urban area received a higher education about smoking cessation, and the healthy conception was also changing with the urbanization.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Results in research suggested that the rate of smoking might experience further decreases in areas with a heightened potential of urbanization. 24 People in the urban area received a higher education about smoking cessation, and the healthy conception was also changing with the urbanization.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of adolescents’ current smoking, the association was more pronounced among male and junior high school students, regardless of the type of tobacco message exposure. Given that this population has a dominant smoking rate 33 , both increased anti-tobacco and reduced pro-tobacco messages could have notable benefits on male students. For junior high school students, their immature physiology and psychology may result in higher sensitivity to both tobacco promotion and tobacco control information.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of adolescents' current smoking, we found that the association was more pronounced among male and junior high school students, regardless of type of tobacco message exposure. A possible reason could be that the existing tobacco promotion and control information mainly aimed at males, given the fact that this population has a dominant smoking rate [32]. Therefore, both increasing the anti-tobacco and reducing the pro-tobacco message exposure could have considerable benefits on male students.…”
Section: Discussionmentioning
confidence: 99%